2011
DOI: 10.1152/jn.00291.2011
|View full text |Cite
|
Sign up to set email alerts
|

Sound frequency representation in primary auditory cortex is level tolerant for moderately loud, complex sounds

Abstract: Pienkowski M, Eggermont JJ. Sound frequency representation in primary auditory cortex is level tolerant for moderately loud, complex sounds. J Neurophysiol 106: 1016 -1027, 2011. First published June 8, 2011 doi:10.1152/jn.00291.2011The distribution of neuronal characteristic frequencies over the area of primary auditory cortex (AI) roughly reflects the tonotopic organization of the cochlea. However, because the area of AI activated by any given sound frequency increases erratically with sound level, it has g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 55 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…than high intensities, at least for spectrally sparse stimuli (Galván et al 2001;Pienkowski and Eggermont 2011).…”
Section: Resultsmentioning
confidence: 99%
“…than high intensities, at least for spectrally sparse stimuli (Galván et al 2001;Pienkowski and Eggermont 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Pienkowski and Eggermont (2011) have reported a level-invariant representation of the spectral energy of acoustic stimuli based on MUA and LFP signals only for responses to complex sounds, but not for single tone pips, as used in this study [74]. Due to the spectral energy distribution of complex tones it has been suggested that competitive interactions between cortical columns account for the spectral integration [14,75].…”
Section: Discussionmentioning
confidence: 98%
“…Thus, by the level of auditory cortex, complex sounds may be represented in a largely intensity-independent, "object-oriented" fashion (Billimoria, Kraus, Narayan, Maddox, & Sen, 2008;Pienkowski & Eggermont, 2011c; for a review, see Barbour, 2011), particularly during attentive listening (Ding & Simon, 2012;Mesgarani & Chang, 2012), although the basis for such representations may begin to emerge in the cochlear nucleus (Blackburn & Sachs, 1990; for a review, see Young, 1998). Thus, by the level of auditory cortex, complex sounds may be represented in a largely intensity-independent, "object-oriented" fashion (Billimoria, Kraus, Narayan, Maddox, & Sen, 2008;Pienkowski & Eggermont, 2011c; for a review, see Barbour, 2011), particularly during attentive listening (Ding & Simon, 2012;Mesgarani & Chang, 2012), although the basis for such representations may begin to emerge in the cochlear nucleus (Blackburn & Sachs, 1990; for a review, see Young, 1998).…”
Section: Neural Codes For Loudnessmentioning
confidence: 99%